The Model Grows the Society of Solving Through Financial Literates and Investment Portfolio on Fisheries-Traders in Surabaya Indonesia - Fatihudin, Didin; Hidajat, Sjamsul; Holisin, Iis (International Journal of Economics and Financial Issues, 2017)
This study aims to find a model to develop self-saving independence among traders and fishermen through financial literacy and investment portfolio. How many Traders-Fishermen know, allocate their income to various investment instruments, such as deposits, houses, land/rice fields, gold, plantations, bonds, stocks, mutual funds, pension funds and others. Explorative research method, Triangulation, qualitative approach. The results showed that traders and fishermen are still a few who know the type of saving instruments. A small portion of income has been deposited in savings, gold, land and houses. Although already bought land, the house by way of credit, deposits had never been. Banking is considered a lot of time-consuming business work. Respondents do not understand the investment portfolio. The respondents' income is mostly used for daily needs, adding capital goods and working capital. Merchants buy merchandise. Fishermen buy fishing gear, boat machine. Most Traders-Fishermen use the instrument 'arisan' only, easier transactions than banking. In the theory of financial planning, the financial allocation of income, preferably 40 percent consumption, 30 percent loan, 15-20 percent savings, 5 percent insurance, 5 percent just in case. Independence of savings already exists although still in the form of social gathering. Need to introduce more investment portfolios. Keywords: Savings, Financial Literacy, Investment Portfolio JEL Classifications: C32; O13; O47